Fast and cost-effective mining of microsatellite markers using NGS technology: an example of a Korean water deer Hydropotes inermis argyropus. - Jeong-Nam Yu; Changman Won; Jumin Jun; Youngwoon Lim; Myounghai Kwak (PLoS ONE, 2011)
BACKGROUND: Microsatellites, a special class of repetitive DNA sequence, have become one of the most popular genetic markers for population/conservation genetic studies. However, its application to endangered species has been impeded by high development costs, a lack of available sequences, and technical difficulties. The water deer Hydropotes inermis is the sole existing endangered species of the subfamily Capreolinae. Although population genetics studies are urgently required for conservation management, no species-specific microsatellite marker has been reported. METHODS: We adopted next-generation sequencing (NGS) to elucidate the microsatellite markers of Korean water deer and overcome these impediments on marker developments. We performed genotyping to determine the efficiency of this method as applied to population genetics. RESULTS: We obtained 98 Mbp of nucleotide information from 260,467 sequence reads. A total of 20,101 di-/tri-nucleotide repeat motifs were identified; di-repeats were 5.9-fold more common than tri-repeats. [CA](n) and [AAC](n)/[AAT](n) repeats were the most frequent di- and tri-repeats, respectively. Of the 17,206 di-repeats, 12,471 microsatellite primer pairs were derived. PCR amplification of 400 primer pairs yielded 106 amplicons and 79 polymorphic markers from 20 individual Korean water deer. Polymorphic rates of the 79 new microsatellites varied from 2 to 11 alleles per locus (H(e): 0.050-0.880; H(o): 0.000-1.000), while those of known microsatellite markers transferred from cattle to Chinese water deer ranged from 4 to 6 alleles per locus (H(e): 0.279-0.714; H(o): 0.300-0.400). CONCLUSIONS: Polymorphic microsatellite markers from Korean water deer were successfully identified using NGS without any prior sequence information and deposited into the public database. Thus, the methods described herein represent a rapid and low-cost way to investigate the population genetics of endangered/non-model species.